Perceived impact of heat stress on health and productivity of tropical female garment workers– a comparison between cool and hot months - Vabotra Chea; Sarin Chan; Natalia Borzino; Min Sze Pearl Tan; Jason Kai Wei Lee; Kinnaleth Vongchanh (BMC Public Health)
Abstract Background Challenging work conditions, characterized by high temperatures and humidity without the availability of adequate cooling systems, can put garment workers at an increased risk of heat stress. We examined the impact of heat stress on the health and productivity of young female garment workers, and the heat relief measures they took. Methods We surveyed and compared a total of 753 female responses across three factories in tropical Phnom Penh, Cambodia, between the cool (November 2021 to January 2022, WBGT 25.2 ± 2.0oC) and hot months (April to June 2022, WBGT 29.0 ± 0.8oC). The surveys assessed perceptions of thermal comfort in the workplace, the effects of heat stress on heat-related symptoms and productivity, as well as the heat relief measures taken. Non-parametric tests were used to assess differences in responses between the cool and hot months. Results During hot months, respondents reported an increase in heat-related symptoms (68% in cool months vs. 88% in hot months). Common symptoms included thirst (50% vs. 81%, p < 0.001), feeling hot (28% vs. 68%, p < 0.001), and heavy sweating (31% vs. 61%, p < 0.001). The perceived impact on productivity was greater during hot months (59% vs. 68%). Respondents perceived heat degraded their motivation (50% vs. 72%, p < 0.001), task speed (42% vs. 66%, p < 0.001), ability to do physical work (37% vs. 56%, p < 0.001), and understanding of tasks (18% vs. 31%, p < 0.001). Increasing water intake was the most common heat relief measure (87% vs. 95%, p < 0.001), while other strategies such as resting in front of a fan (32% vs. 36%) or pouring water over their head (20% vs. 21%) were similar between the cool and hot months (p > 0.05). Conclusions Even a small increase in temperature could compromise workers’ health and work productivity. Workers had to seek heat relief measures all year round due to constant exposure to high temperatures and humidity. In face of a warming world, it is therefore pertinent that these heat-induced impacts are addressed to safeguard workers’ lives and livelihoods, and to ensure productivity in factories.